66.3k views
20 votes
Solve by using substitution. Express your answer as an ordered pair. 2x+y=-5 y=x+4

1 Answer

5 votes
Answer: (-3, 1)

Explanation:

=> 2x + y = -5 (Eq. 1)
=> y = x + 4 (Eq. 2)

Substitute value of ‘y’ from Eq. 2 in 1 :-

2x + y = -5
2x + (x + 4) = -5
2x + x + 4 = -5
3x + 4 = -5
3x = -5 - 4
3x = -9
x = -9/3
=> x = -3

Therefore, x = -3

Substitute value of ‘x’ in Eq. 2 :-

y = x + 4
y = (-3) + 4
=> y = 1

Therefore, y = 1

This Solution can be written in the ordered form as (-3, 1)
User Lorrene
by
4.8k points